Evaluation of the Transverse Strength and Elastic Modulus of High Impact Denture Base Material - gonca deste; rukiye durkan; perihan oyar (Mashhad University of Medical Sciences, 2020)
Introduction: High fracture resistance of prostheses are well accepted by both patients and dentists to have a proper restoration of the dentition. The research  designated  assess polymerization  time  effect distinct   and complete temperatures on mechanical properties (denture base resin) of a high strength. The research  purpose is to assess  and compare the procedure  used in  polymerization distinct effect autoclave on the elastic modulus  and transverse strength of a high strength acrylic resin  to the conventional heat polymerizing. Methods: Rectangular sample of ninety-one  polymarised high heat  strength denture base resin  were created.  Polymerized  sample done by hot water regarded as  control group  and the other groups were polymerized in autoclave at different temperatures and time lenghts. After deflasking of sample before procedure it was kept  forty eight hours in water. Three parameters were used  when conducting  transverse strength test bending using calibrated  universal testing machine  with a  load of 500 kg cell and a crosshead speed of 5 mm/min. One-way ANOVA was used in assessing transverse strength and elastic modulus data.  And for  comparison   of the groups application of Tukey HSD trial  has been seen appropriate (p <0.05). Results: Specimens that polymerized by autoclave at 130ºC for 20 and 30 minutes showed significantly better characteristics compared to the other groups. Conclusion:  Upgrading of  base resins  transverse strength is required  because the  research  indicated autoclave polymerization at 130°C for 20 and 30 minutes may be an alternative polymerization method.